TEMPO‐Catalyzed Aerobic Oxidative Coupling of Thiols for Metal‐Free Formation of S−N/S−S Bonds. Issue 3 (30th January 2017) - Yang, Liting; Li, Shuding; Dou, Yingchao; Zhen, Shan; Li, Heng; Zhang, Panke; Yuan, Bingxin; Yang, Guanyu
Abstract: Catalytic syntheses of organic sulfenamides and disulfides have great significance and value in synthetic chemistry and bioscience. To establish a versatile and efficient technology for such reactions, an aerobic oxidative coupling method for the formation of S−N and S−S bonds, using TEMPO as a catalyst and O2 as an oxidant, has been successfully developed. Reactions showed good tolerance toward various amines and thiols. Sulfenamides were produced in up to 99 % yield, while disulfides were formed in up to 97 % yield in one‐pot syntheses. Activation of the N−H bond by 2, 2‐disbenzothiazoledisulfide showed the great potential in organic synthesis. Abstract : An aerobic oxidative coupling method for the formation of S−N and S−S bonds, using TEMPO as a catalyst and O2 as an oxidant, has been developed. Reactions showed good tolerance toward various amines and thiols, and sulfenamides were produced in up to 99% yield in a one‐pot synthesis.